THE POLITICAL "FRONT" IN ABKHAZIA AND SOUTH OSSETIA - Yulia Semenovna Ulyanova (Современная наука и инновации)
Neither Abkhazia nor South Ossetia has not escaped the activities in the period of perestroika of mass politicized associations in support of socio-political changes. If to the «Forum» and «Front» collapse of the USSR acted, then the only «front», which actually was a party in Abkhazia, and in South Ossetia «unit» of parties. The main objectives of modern politicized movements - are to overcome the negative social effects that can be achieved by combining the efforts of visionary politicians, which are responsible to the people.